Perancangan Buku Cerita Matematika Geometri untuk Kelas Tiga Sekolah Dasar dengan Strategi Visual Spasial - Sara Ratriansari; Birmanti Setia Utami; Michael Bezaleel (Citradirga : Jurnal Desain Komunikasi Visual dan Intermedia, 2019)
Mathematics is one of the subjects that must be completed in elementary schools. However, mathematics gets stereotyped in children, so mathematics is a difficult and unpleasant counting lesson. This is because of children's learning methods are not appropriate in understanding abstract mathematical concepts. One of the abstract concepts in mathematics is geometry material for third grade elementary school. Geometry requires visual spatial ability in the process of solving difficulties. However, in practice, the process of learning mathematics still uses a lot of media that is not sharpening children's visualization like conventional book. This is also caused by the lack of other teaching aids. Therefore, using a visual spatial strategy, this study uses teaching aids using visual techniques that are interesting and stimulate the visual spatial abilities in children. This study uses a qualitative method with linear flow. The flow of research discusses the collection of problems, collecting primary data through interviews and secondary data through the study of literature and direct observation, data analysis, design, testing and gathering conclusions. This research supports to improve visual spatial abilities in the process of learning mathematics in ways that are attractive to children. The results of the study will describe the suitability and potential of teaching aids designed with the learning needs of geometry in third grade elementary school children.